Role of cognitive impairments and decreased muscle strength in cardiovascular mortality of 55 years and older population - A. E. Imaeva; A. V. Kapustina; S. A. Shalnova; Yu. A. Balanova; V. M. Shkolnikov (Российский кардиологический журнал, 2019)
Aim. To assess possible associations of impaired cognitive function (CF) with muscle strength, determined using handgrip test, as well as their role in cardiovascular mortality (CVM) in a population of 55 years and older.Material and methods. This work was carried out in the framework of the prospective cohort study “Stress, aging and health”. During the study 1876 men and women aged 55 and older were examined. CF was estimated on the Mini-Mental State Examination (MMSE) scale, the decrease of CF was recorded with scores of less than 24 points (overall 30 points). Muscle strength was estimated according to handgrip test. To assess the role of muscle strength in CVM, handgrip test values, corresponding to the first quintile, were used — less than 19 kg for women, and less than 32 kg for men. Mortality was estimated on the basis of death register using standard methods. During the observation, 247 deaths from cardiovascular diseases were recorded.Results. The study included 1876 participants aged 55 years and older (48% of men and 52% of women). CF parameters according to the MMSE questionnaire were within the normal range of more than 80% of those examined. According to the results of the regression analysis, only low values of handgrip test (at the level of 1 quintile) were reliably associated with cognitive impairments (p<0,05). These associations were more pronounced in women (odds ratio (OR): 3,17; 95% CI 1,31¬7,69), compared with men (OR: 2,41; 95% CI 1,05-5,54). In 55 years and older men, cognitive impairments were significantly associated with CVM (OR: 1,97; 95% CI 1,40-2,78) and reduced muscle strength (OR: 1,63; 95% CI 1,18-2,25). Among women, only reduced muscle strength significantly increased the risk of CVM (OR: 1,77; 95% CI 1,19-2,61). The simultaneous presence of these pathologies was reliably associated with CVM.Conclusion. The presented study revealed significant associations of cognitive impairments with reduced muscle strength. The presence of both pathological disorders is prognostically unfavorable for cardiovascular death in a population of 55 years and older (both among men and women). Thus, it is recommended to consider the possibility of including of muscle strength and cognitive functioning assessment in prognostic scales.